Gossypol Inhibits Non-small Cell Lung Cancer Cells Proliferation by Targeting EGFRL858R/T790M - Wang, Yuwei; Lai, Huanling; Fan, Xingxing; Luo, Lianxiang; Duan, Fugang; Jiang, Zebo; Wang, Qianqian; Leung, Elaine Lai Han; Liu, Liang; Yao, Xiaojun (Frontiers in Pharmacology, 2018)
Background: Overexpression of epidermal growth factor receptor (EGFR) has been reported to be implicated in the pathogenesis of non-small cell lung cancer (NSCLC). Several EGFR inhibitors have been used in clinical treatment of NSCLC, but the emergence of EGFRL858R/T790M resistant mutation has reduced the efficacy of the clinical used EGFR inhibitors. There is an urgent need to develop novel EGFRL858R/T790M inhibitors for better NSCLC treatment. Methods: By screening a natural product library, we have identified gossypol as a novel potent inhibitor targeting EGFRL858R/T790M. The activity of gossypol on NSCLC cells was evaluated by cell proliferation, cell apoptosis and cell migration assays. Kinase activity inhibition assay and molecular docking were used to study the inhibition mechanism of gossypol to EGFRL858R/T790M. Western blotting was performed to study the molecular mechanism of gossypol inhibiting the downstream pathways of EGFR. Results: Gossypol inhibited the cell proliferation and cell migration of NSCLC cells, and induced caspase-dependent cell apoptosis of NSCLC cells by upregulating the expression of pro-apoptotic protein BAD. Molecular docking revealed that gossypol could bind to the kinase domain of EGFRL858R/T790M with good binding affinity through hydrogen bonds and hydrophobic interactions. Gossypol inhibited the kinase activity of EGFRL858R/T790M with EC50 of 150.1 nM. Western blotting analysis demonstrated that gossypol inhibited the phosphorylation of EGFR and its downstream signal pathways in a dose-dependent manner. Conclusion: Gossypol inhibited cell proliferation and induced apoptosis of NSCLC cells by targeting EGFRL858R/T790M. Our findings provided a basis for developing novel EGFRL858R/T790M inhibitors for treatment of NSCLC.